FERTILITAS TERHADAP PARTISIPASI TENAGA KERJA WANITA DI KABUPATEN PEGUNUNGAN BINTANG - Pramono, Sunardi Eko; Veplun, Dirk; Tebaiy, Vince (Universitas Cenderawasih, 2024)
Fertility is one of the population dynamics in addition to the level of education, age of marriage and family income affecting population growth in a region. The purpose of this study was to analyze the influence of education variables, early marriage age and family income on fertility in Pegunungan Bintang Regency. This research is important to support data-based population policy in Pegunungan Bintang Regency. This study uses a quantitative research approach, the analysis technique used is multiple linear regression analysis. The population in this study were all married women in Oksibil District, Pegunungan Bintang Regency with 258 respondents. With a research sample sample used as many as 60 people with the analysis technique used is multiple linear regression analysis. The results showed that education has a significant effect on labor fertility in Oksibil District, Pegunungan Bintang Regency. This means that, an increase in the level of education results in a lower birth rate. Age of marriage has a significant effect on labor fertility in Oksibil District, Pegunungan Bintang Regency. This means that, the younger a person marries, the more likely it is to have many children. Family income has a significant effect on labor fertility in Oksibil District, Pegunungan Bintang Regency. This means that, the higher the income, the perception of the value of children will decrease so that fertility will decrease.